UPAYA MELATIH KEDISIPLINAN ANAK USIA 5-6 TAHUN MELALUI KEGIATAN BERMAIN LALU LINTAS PADA TK PGRI KECAMATAN TANETE RIATTANG BARAT KABUPATEN BONE - DARMAWATI, DARMAWATI; Widyawati; Sitti Fatimah (EDUCHILD (Journal of Early Childhood Education), 2025)
This study aims to: 1) determine the description of the discipline of children aged 5-6 years in PGRI Kindergarten, West Tanete Riattang District, Bone Regency. 2) determine the application of traffic play in training the discipline of children aged 5-6 years through traffic play activities in PGRI Kindergarten, West Tanete Riattang District, Bone Regency. The type of research used in this study is qualitative research with a phenomenological research method, which was carried out in PGRI Kindergarten, West Tanete Riattang District, Bone Regency with a sample of 10 children, and the approach used in this study is a pedagogical approach. The collection technique uses observation, interview, and documentation techniques to obtain comprehensive information. The results of the study show that: 1) The description of the discipline of children aged 5-6 years in PGRI Kindergarten at the beginning can be seen from the fact that there are still children who are not yet able to obey the rules, the ability to control themselves, be responsible in activities, consistent discipline behavior, and maximum compliance with teacher instructions in disciplinary behavior in early childhood. 2) By providing traffic play activities, it can train and improve the discipline of children aged 5-6 years. Through the introduction and play activities of traffic signs, children become more familiar with the rules, accustomed to following instructions, able to wait their turn, and demonstrate orderly behavior during the activity. Therefore, traffic play activities are an effective learning strategy and are in accordance with the characteristics of early childhood in instilling the value of discipline. Keywords: Children's Discipline, Traffic Play, Early Childhood